Kinerja Keuangan Perbankan dalam Menghasilkan Profitabilitas di Saat Pemulihan Ekonomi Nasional - Sabrina, Nova; Putri, Ancala Laras; Oktarici, Eddo Nanda (Medan Resource Center, 2023)
This article aims to discuss the financial performance of banks in generating profitability during the national economic recovery. Profitability is the ability of a company to create maximum profit efficiently and effectively. Profitability is also a benchmark for assessing a bank. This study aims to analyze the influence of Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR), Operating Costs and Operating Income (BOPO) and Profitability as factors that influence BUMN Banks conducting Initial Public Offering (IPO) policies for the 2019-2019 period. 2021. This study also examines Return On Assets (ROA) as a mediating variable in the research model. The sample selection method used in this study was a purposive sampling method with a total of 4 state-owned banks that met the criteria. The type of data used is secondary data and cross sectional data analysis data and the Interaction Moderating Test with the help of Statcal software. The conclusion from this study is that the Capital Adequacy Ratio (CAR) and Loan to Deposit Ratio (LDR) have a positive effect on Return On Assets (ROA) while BOPO has a negative effect on Return On Assets (ROA). The Capital Adequacy Ratio (CAR) has a positive effect on Return On Investment (ROI) while the Loan to Deposit Ratio (LDR) and BOPO have a negative effect on Return On Investment (ROI). On the other hand, Return On Assets (ROA) is unable to mediate the Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR) and BOPO to Return On Investment (ROI).